A new index to assess the severity of Lichen planus in clinical practice - Aleksandr V. Patrushev; Aleksei V. Samtsov; Aleksei V. Sukharev; Aleksandr A. Minchenko; Maxim V. Mamunov (Vestnik Dermatologii i Venerologii, 2020)
Purpose.Development and validation of the severity index of lichen planus (LP).